Effect of Sedimentor Concentration and Deposition Time on the Quality Pectin Extraction Results of Durian Peel - Deasi Indrawati Putri Lumbantoruan; Sentosa Ginting; Ismed Suhaidi (Universitas Sumatera Utara, 2014)
Pectin is high value functional foods are widely useful in the formation of a gel and a stabilizer on the making of jelly, jam and marmalade. This research was aimed to know the effect of sedimentor concentration and deposition time on the quality of pectin extracted from durian peel and to know how to extract pectin and add economic value on durian peel waste.This research was conducted using a completely randomized design with two factors, namely the concentration of the alcohol ; 65%, 75%, 85% and 95% and the settling time, 14 hours, 16 hours, 18 hours and 20 hours. The parameters analyzed were yield, moisture content, ash content, equivalent weight, methoxyl content and galacturonic levels. The results showed that the concentration of alcoholhad highly significant effect on yield, moisture content, equivalent weight, methoxyl content and galakturonat levels, and provided no effect on ash content. Deposition time gave highly significant effect on yield, moisture content, equivalent weight, methoxyl content and galakturonat levels and provided no effect on ash content. Interactions of deposition time and concentration gave highly significant effect on yield, methoxyl content and galakturonat levels, and had no effect moisture content, ash content and equivalent weight. Concentration of 95% alcohol and a 20-hour precipitation produce the best quality of durian peel pectin. Keywords: deposition time, durian peel, pectin, sediment concentration